(untitled) (Global Media Journal - German Edition, 2020)
This article investigates how threat narratives and enemy images were constructed at the pan-Arab news TV station, al-Mayadeen, during the station’s first year on air. I argue that the construction of an enemy image takes places as a fine interplay between threat narratives of existing political and ideological positions on the one hand, and current affairs on the other. Al-Mayadeen started broadcasting in 2012, counteracting both the new influential narratives of young activists calling for democracy, and the Sunni Islamist trend that followed; both groups became central elements in a process of ‘Othering’ at al-Mayadeen, dividing the Arab world into ‘good’ and ‘bad’. Al-Mayadeen relaunched the question of Palestine, while the well-known threat narrative of Israel was equally promoted although adjusted to ongoing political and military developments in the region. Integrating the rising new actor, the Islamic State, a renewed enemy image was constructed where Israel and the Islamic State came to constitute two faces of the same enemy.